Antibacterial activity of human mesenchymal stem cells mediated directly by constitutively secreted factors and indirectly by activation of innate immune effector cells. (8th November 2019) - Chow, Lyndah; Johnson, Valerie; Impastato, Renata; Coy, Jonathan; Strumpf, Alyssa; Dow, Steven
Abstract: Mesenchymal stem cells (MSC) have been shown to improve wound healing and suppress inflammatory immune responses. Newer research also indicates that MSC exhibit antimicrobial activity, although the mechanisms underlying this activity have not been fully elucidated. Therefore, we conducted in vitro and in vivo studies to examine the ability of resting and activated MSC to kill bacteria, including multidrug resistant strains. We investigated direct bacterial killing mechanisms and the interaction of MSC with host innate immune responses to infection. In addition, the activity of MSC against chronic bacterial infections was investigated in a mouse biofilm infection model. We found that MSC exhibited high levels of spontaneous direct bactericidal activity in vitro. Moreover, soluble factors secreted by MSC inhibited Staphylococcus aureus biofilm formation in vitro and disrupted the growth of established biofilms. Secreted factors from MSC also elicited synergistic killing of drug-resistant bacteria when combined with several major classes of antibiotics. Other studies demonstrated interactions of activated MSC with host innate immune responses, including triggering of neutrophil extracellular trap formation and increased phagocytosis of bacteria. Finally, activated MSC administered systemically to mice with established S. aureus biofilm infections significantly reduced bacterial numbers at the wound site and improved wound healing when combined with antibiotic therapy. These results indicate that MSC generate multiple direct and indirect, immunologically mediated antimicrobial activities that combine to help eliminate chronic bacterial infections when the cells are administered therapeutically. : Abstract : Human bone marrow MSC secrete factors that interact synergistically with antibiotics to media direct bacterial killing. Activation of MSC enhances indirect mechanisms of bacterial killing in a mouse biofilm infection model, and facilitates increased anti bacterial activity of neutrophils.